Integrating ICT in English Language Learning: Students’ Perceptions of a State University in Jambi Province: Students’ Perceptions of a State University in Jambi Province - Dwi Oktalia; Ngadiso Ngadiso; Slamet Supriyadi (International Journal of Language Teaching and Education, 2018)
This research was done in order to know students‘ perception toward integrating ICT in English Language Learning and also to find out problem that may faced by students during the ICT integration. This research used quantitative method in order to describe students‘ perception toward the use of ICT in ELL. This research involved English students from a state university in Jambi province as the respondents. The data were collected by using questionnaires adapted from Chutopama (2004). The questionnaires consisted of items related to the use of ICT for their learning, their reason(s) of using ICT, as well as the problem(s) encountered through the use of ICT for the learning. After that, the data were analyzed by using SPSS 16 that pointed at a point in which the students agreed that ICT is beneficial for their learning process, especially in terms of accessing information for learning. Nevertheless, employing ICT in learning needs to be supported by sufficient equipment, and needs to educate the students to be an agile user for better, more effective, and more efficient process of learning.